Sebatakgomo: Migrant organization, the ANC and the Sekhukhuneland Revolt - Delius, P. (My University)
In the 1940s and 1950s in reserve and trust area from the Zoutpansberg to the Ciskei bitter battles were fought against first Betterment Schemes and then Bantu Authorities. Communities believed - with good reason - that these state initiatives posed a mortal threat to their residual, but cherished, economic and political autonomy. These episodes are usually treated under the rubric of rural or peasant resistance but the centrality of migrant labour to the South African political economy has always undermined simple divisions between town and countryside. A closer examination shows that in virtually every instance of resistance urban-based migrant organizations played vital roles. Yet this is difficult to explain for groups like the Zoutpansberg Cultural Association, the Bahurutshe Association or the Mpondo Association step almost entirely unheralded onto the stage. We have the barest idea of the long history of migrant organization which preceded their part in these events. It has also become commonplace in the literature on 'rural resistance' to suggest that the ANC, while not entirely insensitive to rural issues in the 194Os and 1950s, nonetheless failed to establish effective rural organization and played at best a marginal role in the various revolts. This conclusion is partly based on the sparseness of Congress branches in the countryside. But it has been arrived at without any systematic attempt to examine a crucial question. Did migrants and their organizations provide a partly unseen but effective bridge between the ANC, the SACP and rural politics? These gaps in our understanding of 'rural resistance' will not easily be filled . This article, however, attempts to provide some illumination of these issues by means of a study of the role of migrants in the Sekhukhuneland Revolt of 1957 — 1961. To give some indication of the destination of the argument, the evidence suggests that a movement established in 1954 from within the ANC and the SACP - Sebatakqqmg - won widespread migrant support and played a key role in organizing and sustaining the resistance in the eastern Transvaal. The journey to this conclusion will, however, be long and prone to detour - for in order to be able to explain the interaction between migrants, the ANC, and rural conflict in the 1950s it is necessary to trace the changing patterns of Pedi employment and association from at least the 1930s.
African Studies Seminar series. Paper presented. No dates given in the paper. No citations in copy. Marked 'Additional Seminar paper' and on the 1st page of text as 'informal'.
Keywords: African National Congress; Pedi (African people); Migrant labor. South Africa; Transvaal (South Africa)